Rituals of the Byaṅ gter tradition : a collection of explanations - Padma-phrin-las, Rdo-rje-brag Rig-ʼdziṅ II, 1640?-1718 (Bari Longsal Lama, 1980)
Collected rituals and prayers of the Changter (Byan gter) rites of the Nyingmapa sect.